River of hope : Black politics and the Memphis freedom movement, 1865-1954 - Gritter, Elizabeth (Civil rights and the struggle for Black equality in the twentieth century., 2014)
One of the largest southern cities and a hub for the cotton industry, Memphis, Tennessee, was at the forefront of black political empowerment during the Jim Crow era. Compared to other cities in the South, Memphis had an unusually large number of African American voters. Black Memphians sought reform at the ballot box, formed clubs, ran for office, and engaged in voter registration and education activities from the end of the Civil War through the Brown v. Board of Education decision of 1954. In this groundbreaking book, Elizabeth Gritter examines how and why black Memphians mobilized political.